Comparison of clinical effects of aspherical monofocal and Tecnis ZMB00 multifocal intraocular lenses in patients with age-related cataract - Dan Han; Xinli Ma; Jiayue Gao; Ziwei Xu; Fa Liu (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the clinical effects and outcomes in patients implanted with aspheric monofocal and multifocal intraoeular lens. Method: This study was conducted from January 2020 to January 2023 at Harbin 242 Hospital in China, using a prospective randomized case-control design. The research subjects were hospitalized patients with age-related cataracts, randomly divided into a control group A receiving single focus intraocular lenses and an intervention group B receiving multi focus intraocular lenses. The visual acuity, visual quality, glasses independence rate, vision related quality of life, and incidence of complications were compared between the two groups. Data analysis was conducted using SPSS 25 software. Results: Of the 100 patients, 50(50%) were in group A; 28(56%) females and 22(44%) males with mean age 63.25±7.59 years. The other 50(50%) patients were in group B; 26(52%) females and 24(48%) males with mean age 62.03±6.74 years (p>0.05). Group B patients had higher uncorrected visual acuity at 1 week, 1 month and 3 months post-surgery (p<0.05), higher vision-related quality of life at 3 months post-surgery (p<0.05), and higher rate of spectacle independence (p<0.05) than group A. However, group B had lower modulation transfer function at 30 and 45 cycles per degree, and lower contrast sensitivity function at 3 and 6 cycles per degree than group A (p<0.05). The incidence of halo and glare in group B was higher than group A (p<0.05). Conclusion: The multifocal intraoeular lens outperformed the aspherical monofocal intraoeular lens in improving the vision-related quality of life and rate of spectacle independence. However, it had dark vision defects and optical side-effects. Key Words: Cataract, Intraocular lenses, Visual acuity, Treatment outcome.